Efficiency of services in CEE countries—case study of Poland and Belarus - Skąpska, Elżbieta; Rollnik-Sadowska, Ewa (Economics and Business Review, 2020)
The aim of the paper is to identify determinants of the efficiency of service companies from two Central and Eastern European (CEE) countries4—Poland and Belarus. These transition economies represent different economic and systemic conditions. That is why it is worth analyzing whether external conditions determine internal efficiency factors in service companies. In order to achieve that aim quantitative research was conducted among 305 Polish and Belarusian service enterprises. The research results presented significant differences in responses between the two countries. For Polish enterprises the main determinants of efficiency were above all connected with competent and skilled staff. Belarussian companies regarded as efficiency factors which determine the demand level by means of access toward foreign markets and possibilities of internationalization. It proves that CEECs are not homogeneous and they represent different levels of economic development as well as the different conditions of running a business.